1995
DOI: 10.1016/0029-7844(95)93704-4
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-8 Synthesis and the Onset of Labor

Abstract: Interleukin-8 is critically involved in the process of parturition in humans. Interleukin-8 concentrations in the myometrium, decidua, and membranes correlated strongly with the observed MMP-8 and MMP-9 concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
111
1
5

Year Published

2003
2003
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(127 citation statements)
references
References 30 publications
9
111
1
5
Order By: Relevance
“…13 In parallel, upregulation of pro-inflammatory cytokines mRNA expression of Interleukin-1 b (IL-1b, IL-6, C-X-C motif ligand (CXCL) 8 and C-C motif ligand (CCL) 2 was observed in the myometrium of healthy labouring women. [14][15][16][17][18] Our recent data confirmed these findings and revealed a more extensive list of up-regulated cytokine and chemokine proteins (CXCL8, CXCL1, CCL2, CCL7, IL-9, IL-18, IL-1RN, tumor necrosis factor alpha (TNFa) and granulocyte colony-stimulating factor (G-CSF)) in healthy TL human myometrial tissue samples, while also detecting a higher number of macrophage and neutrophil infiltrate. 7,19 The trigger that elevates cytokines in the myometrium of healthy women during labour remains largely elusive.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…13 In parallel, upregulation of pro-inflammatory cytokines mRNA expression of Interleukin-1 b (IL-1b, IL-6, C-X-C motif ligand (CXCL) 8 and C-C motif ligand (CCL) 2 was observed in the myometrium of healthy labouring women. [14][15][16][17][18] Our recent data confirmed these findings and revealed a more extensive list of up-regulated cytokine and chemokine proteins (CXCL8, CXCL1, CCL2, CCL7, IL-9, IL-18, IL-1RN, tumor necrosis factor alpha (TNFa) and granulocyte colony-stimulating factor (G-CSF)) in healthy TL human myometrial tissue samples, while also detecting a higher number of macrophage and neutrophil infiltrate. 7,19 The trigger that elevates cytokines in the myometrium of healthy women during labour remains largely elusive.…”
Section: Introductionsupporting
confidence: 79%
“…36 Two CXC family chemokines (CXCL1 and CXCL8) are well known for their strong chemoattractant activity on neutrophils, and their expression in human myometrium during spontaneous labour was reported and confirmed by many research groups. 14,37,38 Recent reports of transcriptome data in spontaneous human labouring myometrial samples identified IL-6, CXCL1 and CXCL8 as highly expressed genes, with CXCL8 exhibiting the highest fold change in TL compared to term not-in-labour samples. 3,37 In line with our observations, Hua et al 31 showed that mechanical stretch augmented the expression of various chemokines in primary human myometrial myocytes including CCL2, CXCL8 and CXCL1.…”
Section: Discussionmentioning
confidence: 99%
“…The chemokine IL-8 is largely responsible for the influx of leukocytes into uterine tissues, where it induces their degranulation and release of MMPs (Osmers et al 1995). MMPs are also produced by the cervix itself (Stygar et al 2002), as well as the placenta and fetal membranes (Xu et al 2002).…”
Section: Nf-kb Regulates Matrix Metalloproteinase Expressionmentioning
confidence: 99%
“…However, it remains unclear whether the inflammatory infiltration of the myometrium is a cause or consequence of labour. Human studies show that levels of IL-8 (Table 1) rise with established labour only (Osmers 1995, Elliott et al 2001, Kemp et al 2002a. In rodent pregnancies, it seems apparent that the inflammatory infiltration precedes the onset of labour (Mackler 1999, Shynlova et al 2012b), but various groups have depleted pregnant animals of neutrophils (Timmons 2006) or studied animals with no mast cells (Menzies et al 2011), without delaying labour onset.…”
Section: Myometrial Inflammationmentioning
confidence: 99%